2022
DOI: 10.1186/s12929-022-00857-4
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of reversible cerebral vasoconstriction syndrome

Abstract: Reversible cerebral vasoconstriction syndrome (RCVS) is a complex neurovascular disorder being recognized during the past two decades. It is characterized by multiple abrupt severe headaches and widespread cerebral vasoconstrictions, with potential complications such as ischemic stroke, convexity subarachnoid hemorrhage, intracerebral hemorrhage and posterior reversible encephalopathy syndrome. The clinical features, imaging findings, and dynamic disease course have been delineated. However, the pathophysiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 126 publications
2
45
0
5
Order By: Relevance
“…This relationship may be supported by the effects of COVID -19 on the vascular endothelium [ 124 ], with the impairment of cerebral autoregulatory mechanisms representing the pathophysiological process of both RCVS and PRES [ 17 , 21 ]. Some studies reported that SARS-CoV2 may enter the CNS [ 125 , 126 ] and exert its effects on the endothelium [ 124 ], while others demonstrated that it binds to the angiotensin-converting enzyme 2 (ACE2) receptor, which is highly expressed in neurons and glial cells [ 125 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This relationship may be supported by the effects of COVID -19 on the vascular endothelium [ 124 ], with the impairment of cerebral autoregulatory mechanisms representing the pathophysiological process of both RCVS and PRES [ 17 , 21 ]. Some studies reported that SARS-CoV2 may enter the CNS [ 125 , 126 ] and exert its effects on the endothelium [ 124 ], while others demonstrated that it binds to the angiotensin-converting enzyme 2 (ACE2) receptor, which is highly expressed in neurons and glial cells [ 125 ].…”
Section: Discussionmentioning
confidence: 99%
“…Key elements are focal vasoconstrictions of brain vessels, which appear in angiographic studies as intermittent focal narrowing, causing the “sausage on a string appearance”. A proposed model suggests that the disease may be caused by an interplay of endothelial dysfunction, oxidative stress, and sympathetic overactivity which results in BBB disruption and cerebral vascular tone dysregulation [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The sympathetic system around the vessels has been proposed to be responsible for the abrupt onset of both headache and vasospasm in patients with thunderclap headache (64). Vasospasm, which refers to a reversible process of a localized smooth muscle contraction of the blood vessel walls resulting in segmental luminal narrowing, can be an expression of high sympathetic tone (6567). However, vasospasm only appears in RCVS but not in primary thunderclap headache.…”
Section: Pathophysiologymentioning
confidence: 99%
“…2 As cerebral arteries are densely innervated, the release of norepinephrine or neuropeptide Y from the sympathetic nerve endings may cause vasoconstrictions. 3 Angiographically, SAH-induced vasospasm is more commonly long-segmental and mainly around the bleeding focus, compared with the multiple, short-segmental, and diffuse changes seen in RCVS. 4 However, by analogy, RCVS is treated by nimodipine, and in some rare cases, the use of milrinone might be considered.…”
mentioning
confidence: 99%
“…4 However, by analogy, RCVS is treated by nimodipine, and in some rare cases, the use of milrinone might be considered. 3…”
mentioning
confidence: 99%